Pengaruh Jenis Nasabah dan Frekuensi Pencairan Pembiayaan terhadap Profit Margin di Bank Pembiayaan Rakyat Syariah (BPRS) Sarana Prima Mandiri Pamekasan - Sundari Aniga; Erie Hariyanto (IQTISHADIA Jurnal Ekonomi & Perbankan Syariah, 2016)
Bank is a financial institution whose main activities to collect funds and distribute funds to the community. Factors that very influence in the bank's success in obtaining profit is by increasing the disbursement frequency of financing and client’s types as one of the factors that influence the amount of profit margin obtained bank. Based on that, then there are two problems who became a study principal in this research as follows: first: Is there any influence of customer type and financing liquefaction frequency towards Profit Margin in BPRS Sarana Prima Mandiri Pamekasan; second, which is the most influential variable on the Profit Margin in BPRS Sarana Prima Mandiri Pamekasan. This Research uses a quantitative approach with research type is multiple linear regression. The amount of data used in this research as many as 20 data taken from published reports of Quarterly Bank Indonesia and published reports BPRS Sarana Prima Mandiri in January 2011 until December 2015. The research results of T Test of the respective T count X1 amounted to 3.184 and variable X2 amounted to 2.475 and T table amounted to 2.101, (X1 = 3.184> 2.101 and X2 = 2.475> 2.101), it can be concluded the results of the partial test (T test) shows that all variables X (Customer type and financing liquefaction frequency) effect on variable Y (Profit Margin) partially significantly ≤ 0.05 X1 (Customer type) greater influence than X2 (financing liquefaction frequency) T count X1 greater  exceeds X2. Equation Y = ( -16.387) 0.399X1 + 0186 + X2 + e, based on multiple regression analysis, the regression coefficient obtained shows, customer type (b1 = 0.399) become the largest independent variables that influence Profit Margin (Y). While base testing the determinant coefficient using the program SPSS acquired adjusted R2 amounted to 0.732 or 73.2% means variable of Customer Type Financing and financing liquefaction frequency affect toward the profit margin amounted to 73.2% while the rest 26.8% influenced by other variables that are not proposed in this research.